Penyelesaian Perkawinan Yang Tidak Memenuhi Syarat Perkawinan Melalui Isbath Nikah - Latupono, Barzah (UI Scholars Hub, 2019)
Marriage is a spiritual bond between a woman and a man as husband and wife to form a happy and eternal family based on the Godhead. For that marriage must be done by fulfilling the rules of marriage law in accordance with applicable law. One of the requirements for a marriage is in accordance with Article 6 of the Marriage Law No. 1 of 1974 is: A person who is still bound by a marriage with another person cannot remarry except to fulfill the provisions of Article 3, (2) and article 4. If this point is not fulfilled, and the parties continue to carry out the marriage, then this marriage is deemed not legitimate. because marriages that are carried out are only legal according to religious law, but will not get recognition from the state, so when they are going to divorce they must keep their marriages. Isbath marriage even though for the purpose of divorce, but of course this will legalize the marriage, because by doing marriage isbat means automatically there is state recognition of marriage that was previously considered illegal.